UPAYA MENINGKATKAN HASIL BELAJAR EKONOMI DENGAN MENERAPKAN MODEL PEMBELAJARAN KOOPERATIF TIPE (THINK PAIR SHARE) - Laia, Marinus (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2024)
The problem with this research is that students do not actively participate in learning and student learning outcomes tend to be low. The research objectives are 1) To apply the Think Pair Share (TPS) learning model in economics subjects in class X-IPS2 SMA Negeri 1 Amandraya. 2) To improve student learning outcomes by implementing the Think Pair Share learning model in economics subjects in class X-IPS2 SMA Negeri 1 Amandraya. This type of research is Class Action (PTK). The subjects of this research were 25 students in class X-IPS2. The research results showed that there was an increase in student learning outcomes, and students participated more actively in learning, as evidenced by an increase in student learning outcomes from cycle I to cycle II. The think pair share type cooperative learning model involves students working together with their friends, and students working together to solve problems. So it can be concluded that the application of the think pair share type cooperative learning model can improve the learning outcomes of class X-IPS2 students at SMA Negeri 1 Amandraya. The suggestions put forward by the researcher are 1) Students should be able to follow each stage in the think pair share type cooperative learning process because this will be very beneficial for increasing students’ ability to always be active in learning activities in the classroom. 2) Teachers should study the guidelines for implementing think pair share type cooperative learning and implement them in learning. 3) Schools should provide encouragement and introduce learning models that can be used to improve the quality of learning in general and the quality of students. One learning model that can be used is the think pair share cooperative learning.